Molecular identification of a new isolate of actinobacteria ATIS61 and characterization of the protease activities - FADHLIAH AMFAR; Lenni Fitri; SUHARTONO SUHARTONO (Society for Indonesian Biodiversity, 2021)
Abstract. Amfar F, Fitri L, Suhartono. 2021. Molecular identification of a new isolate of actinobacteria ATIS61 and characterization of the protease activities. Biodiversitas 22: 1564-1569. Protease is an enzyme that catalyzes the hydrolysis of peptide bonds in protein. Actinobacteria are one of bacterial groups that is able to produce protease. Actinobacteria are Gram-positive bacteria and mostly aerobic. This study aimed to identify protease-producing actinobacteria ATIS61 isolate using 16S rRNA gene and to characterize the protease activity. This study was experimental research, consisted of amplification and sequencing of the 16S rRNA gene, and protease activity test. The 16S rRNA gene analysis showed that ATIS61 isolate was closely related to Nocardia sp. strain 335427 with a 99.88% similarity and the result of phylogenetic tree construction was related to Nocardia farcinica strain ARS8 with Bootstrap 94%. Protease activity test showed the highest activity was on the eighth day of incubation at 0.115 U/mL. Protease activity based on temperature showed the highest activity at 40°C of 0.156 U/mL and the stability of protease towards temperature was stable at 40°C and 50°C. Protease activity showed that the highest protease activity was at pH 8 of 0.096 U/mL and the highest protease stability was also at pH 8. The addition of HgCl2 showed that it could inhibit protease activity with a value of 0.059 U/mL.